Soul of culture II / Noriza Arzain - Arzain, Noriza (Faculty of Art and Design, 2021)
A lot of things inspired this artist in the minimalism content in art and living substance. People she meets and what things she has seen. According to her perception, “Yesterday is history, tomorrow is a mystery, today is a gift of God, which is why we call it the present. The quotes sang themselves; history teaches us lessons and makes us stronger. Old buildings always inspire artists as a person to learn more about the meaning of life. Desire decides the life we strive for, the determination that we put in to build the artwork that always stands out in the community's eye despite being surrounded by skyscrapers. The true meaning of gems”. The title “Soul of Culture II” represents conservation of cultural heritage is not just about the preservation of material things but rather about safeguarding and sharing heritage for the betterment of people’s lives and the environment. This implies a more proactive view of heritage as an instrument of positive change and reflects a broader geopolitical movement to promote sustainability and wellbeing.